Comparative risk of acute myocardial infarction among users of different anti-osteoporosis drugs in Catalonia, Spain: A propensity matched cohort study using data from the SIDIAP database - Khalid, S; Ali, M; Hawley, S; Judge, A; Arden, N; Van Staa, T; Cooper, C; Javaid, M; Prieto-Alhambra, D (Oxford University Press, 2017)
Recent concerns have been raised on a possible increase in cardiovascular risk associated with strontium ranelate use. We aimed to compare the association between use of different AODs and the risk of acute myocardial infarction (AMI) amongst real-world users of AODs in primary care settings.